Het surrealisme in België 1924-2000 - Canonne, Xavier (Brussel : Mercatorfonds Brussel, 2006)
Baes, Rachel ; Blavier, André ; Bossut, Yves ; Bourgoigne, Paul ; Brenta, Gilles ; Broodthaers, Marcel ; van Bruaene, Geert ; Bury, Pol ; Chavée, Achille ; Colinet, Paul ; Delvaux, Paul ; Dohmen, Léo ; Dotremont, Christian ; Dumont, Fernand ; Galand, Claude ; Goemans, Camille ; Graverol, Jane ; Gutt, Tom ; Hamoir, Irène ; Havrenne, Marcel ; Jamagne, Claudine ; Lacomblez, Jacques ; Lecomte, Marcel ; Lefrancq, Marcel ; Lorent, André ; Magritte, Paul ; Magritte, René ; Mariën, Marcel ; Matton, Jacques ; Mesens, E.L.T. ; Nougé, Paul ; Scutenaire, Louis ; Senecaut, Gilbert ; Servais, Max ; Simon, Armand ; Souris, André ; Stas, André ; Ubac, Raoul ; Wallenborn, Jean ; Wergifosse, Jacques ; Willems, Robert ; de Wouwer, Roger van
boek
Keywords: België